Application of ultrasound pretreatment and glycation in regulating the heat-induced amyloid-like aggregation of β-lactoglobulin. (July 2018) - Zhao, Di; Li, Lin; Xu, Dan; Sheng, Bulei; Qin, Dan; Chen, Juncheng; Li, Bing; Zhang, Xia
Abstract: Ultrasonication and glycation are widely used in the food industry. In this study, we evaluated the independent and combined effects of ultrasound pretreatment (UP) and glycation on the heat-induced amyloid-like aggregation of β-lactoglobulin (β-Lg) by investigating both the fibrillation kinetics and aggregate conformations. Both UP and glycation respectively were found to accelerate the fibrillation process by promoting the denaturation and unfolding behavior of β-Lg according to both the thioflavine-T binding assay. Glycation reduced the fibrillation capacity of β-Lg by reducing the content of β-sheet secondary structures in β-Lg on the basis on circular dichroism spectral measurements. Based on the results of transmission electron microscopy, glycation derived from glucose and lactose suppressed the elongation of fibrils, and β-Lg incubated with maltodextrin was shown to form spherical particle micelles. When applied jointly, UP was found to limit the glycation process by promoting aggregation during the initial heating, which may bury a portion of the glycation sites. According to these findings, UP and glycation are promising methods that can be used independently or jointly to regulate both fibrillation kinetics and fibril conformation in the food industry. Graphical abstract: Image Highlights: Ultrasound pretreatment and glycation changed the fibrillation kinetics of β-lactoglobulin. Glycation changed the aggregates conformation. Ultrasound pretreatment changed the subsequent glycation process when they were used jointly.